2015
DOI: 10.1177/2165079915576931
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress Management and Burnout Interventions in Nursing and Their Implications for Healthy Work Environments

Abstract: This article reports on a literature review of workplace interventions (i.e., creating healthy work environments and improving nurses' quality of work life [QWL]) aimed at managing occupational stress and burnout for nurses. A literature search was conducted using the keywords nursing, nurses, stress, distress, stress management, burnout, and intervention. All the intervention studies included in this review reported on workplace intervention strategies, mainly individual stress management and burnout interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 41 publications
1
82
0
10
Order By: Relevance
“…Organizational interventions guided by perceived effort-reward and job-demand-resources imbalances (Mijakoski et al 2015) have shown success and should be considered valid tools in infection prevention and control. Furthermore, access to mental health services for healthcare workers, including individual psychosocial interventions to address burnout have shown success (Gunusen & Ustun 2010;Nowrouzi et al 2015), and should be considered not simply as part of the commitment to workers health but as an investment in patient outcomes as well.…”
Section: Implications For Nursing and Health Policymentioning
confidence: 99%
“…Organizational interventions guided by perceived effort-reward and job-demand-resources imbalances (Mijakoski et al 2015) have shown success and should be considered valid tools in infection prevention and control. Furthermore, access to mental health services for healthcare workers, including individual psychosocial interventions to address burnout have shown success (Gunusen & Ustun 2010;Nowrouzi et al 2015), and should be considered not simply as part of the commitment to workers health but as an investment in patient outcomes as well.…”
Section: Implications For Nursing and Health Policymentioning
confidence: 99%
“…The ill health of care providers in health results in an immense burden to health financial systems and patient care quality (Wie et al, ). The programmes designed to alleviate the effects of chronic stress among nurses (Henry, ; Nowrouzi et al, ) have a limited role in preventing the occurrence of such and enhancing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, burnout has been recognized as an important occupational risk, especially in professions that have direct contact with users or patients (i.e., physicians, nurses, teachers, prison officers, etc.) (EU‐OSHA, ; Figueiredo‐Ferraz, Grau‐Alberola, Gil‐Monte, & Garcia‐Juesas, ; Nowrouzi et al., ). Freudenberger () described this syndrome as ‘a feeling of failure and an exhausting experience that results from overload relating to demand of energy, personal resources, or spiritual strength’ (p.160).…”
Section: Introductionmentioning
confidence: 99%
“…(Maslach, ). Within these professions, nursing staff have been considered one of the main groups particularly affected by burnout, given the specific characteristics of nursing work (Figueiredo‐Ferraz et al., ; Gil‐Monte, Carretero‐Dios, & Roldán, ; Nowrouzi et al., ). Basically, most nursing activities are focused on care and the relationship with patients and family members, in which the direct contact with diseases, pain and death occurs on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation